Analisis Dampak Perilaku Bullying pada Gangguan Psikologis Korban Bullying Di SMP Negeri 1 Conggeang Tahun 2023 - Ely Walimah; Nivi Daniah (Awatara Publisher, 2025)
Bullying is a form of violent behavior in which there is psychological or physical coercion of a person or group of weaker people. Bullying actions among adolescents are often encountered such as threatening, mocking / insulting and even committing violence between others. The impact of bullying in general is that victims experience psychological disorders. Psychological disorders are a collection of abnormal conditions, both related to physical, and mental. This study aims to determine the impact of bullying behavior on psychological disorders in victims of bullying at SMPN 1 Conggeang in 2023. The method used in this research is qualitative with a type of case study research. To find data researchers use interview, observation, and documentation techniques. From the study, it was found that the form of bullying behavior that occurred at SMPN 1 Conggeang was verbal and physical bullying. The impact of bullying on psychological disorders including victims experiencing prolonged anxiety, fear and depression disorders. The school's efforts in reducing bullying behavior are teachers conducting socialization, counseling & stabilization, and providing character education. The school and family environment are the most important factors for bullying committed by children. Teachers are expected to be able to recognize the characteristics of perpetrators and victims of bullying in order to prevent bullying at school